A study of maslow’s hierarchy of needs theory: esteem needs and organizational commitment among employee at Tenaga Nasional Berhad (TNB) Bentong, Pahang Darul Makmur / Nur Faezah Ramli - Ramli, Nur Faezah (2013)
Hierarchy of need theory or also can be defined as Maslow's Hierarchy, this theory is develop by Abraham Maslow in 1954 that can explain about esteem need. Hierarchies of needs theory are talking about the five basic need of human that need to be satisfied in different aspect. Maslow hierarchy need theory stated that esteem need is talking about the achievement of the individual based on their work. How they are being recognized and respect in their career life. Maslow's Hierarchy need is separated in to five needs and can be classified into two levels which are lower levels and higher levels. Esteem needs are consists of higher-order needs. The Higher-order needs is more focus on the person emotions or feelings. This means, when the basic need is full fill the individual or person has a change to having more in their life. The five needs is Physiological needs, Safety or Security needs , Affiliation or social needs, Esteem needs and the higher needs is Self-Actualization needs (Pattanayak, 2010). Maslow hierarchies explain on how individuals are motivated to full fill their different kind of needs. Those need that explain by Maslow theory is can differentiate into five level needs. The basic or lower or basic need is Physiological needs and follow up by Safety or Security needs, Belongings needs, Esteem need and the higher need is Self- actualization needs. The level of need can separate into categories that lower- order needs and higher -order needs. The lower-order needs consist of Physiological needs and Safety needs. The higher-order needs are consists of love, esteem and self-actualization needs (Pattanayak, et. al.). The lower-order needs need to be satisfy before can go into a higher-order needs. The lower-order needs actually are basic or simple needs that individuals must fulfill in order to live or survive. But in the content of life, lower-order needs are the needs that can 't be excuse because that was the basic requirements for live. The basic things we need for survive or live such as food, warmth, water or air, etc. But in the aspect of Job, the basic needs of workers are consists of the working environment of the job, the salary or working hours. In the lower-order needs also consist of safety needs that influence the individuals. ln the safety needs, individuals are required for the safety of the working environment, job security and benefits or bonus. The basic need or lower-order needs play the important role in order for the individuals or worker to survive in their life. The higher-order needs are consists of Affiliation or Love and belonging needs, esteem needs and Self-Actualization needs (Pattanayak, et. al.). lt's more focus on the person emotions or feelings. This means that, when the basic need is full fill by the individual or person then has change to having more in their life. Esteem need is talking about the achievement of the individual based on their work.